Development of the Flywheel Marketing Model as a Performance Improvement Strategy for Micro, Small and Medium Enterprises (MSMEs) - Khalik, Idham; Siregar, Ade Perdana; Rosyid, Garry Yuesa (Dinasti International Journal of Digital Business Management, 2023)
Economic growth in Indonesia will increase by 3.69% (YoY) in 2021. The increase in economic growth in Indonesia is in line with the growth of the retail business, both direct and online retail businesses. The development of the retail business in Indonesia is in line with technological advances, where internet users in Indonesia have increased. The dominant factor that increases the growth of the e-commerce market value is the increase in the participation of MSMEs. The number of MSMEs in Jambi Province in 2020 decreased 2019, and the resilience of MSMEs to compete in improving their business performance is an essential factor in the growth of MSMEs. The development of digital technology should be able to open up opportunities for MSMEs to be able to improve their business performance. MSME business actors have the potential to develop a more comprehensive marketing network. Business organizations carry out activities intending to maintain and develop themselves, one of which is the implementation of marketing strategies. The success of UMKM as a business organization is seen in its performance with the implementation of the right marketing strategy. The aims of this study are (1) to examine the effect of flywheel marketing on MSME business performance; (2) To examine the effect of marketing flywheel on social presence; (3) to assess the effect of social presence on MSME business performance; (4) Assessing the role of social presence that can mediate the influence of marketing flywheel on MSME business performance; (5) To examine the dominant dimension of social presence that mediates the influence of marketing flywheel on MSME business performance. The data analysis method used is Structural Equation Modeling (SEM) measurements using SmartPLS software. The results of the research are (1) Marketing flywheel shows a significant positive effect on MSME business performance, it is proven that the higher the flywheel marketing implementation in MSMEs, MSME business performance will increase; (2) marketing flywheel shows a significant positive effect on social presence, it is proven that the higher the implementation of marketing flywheel in SMEs, the social presence will increase; (3) social presence shows a significant positive influence on MSME business performance, the more social presence in MSMEs, the MSME business performance will increase; (4) social presence as a mediating influence on the marketing flywheel shows a significant positive effect on MSME business performance, where social presence is considered a variable that strengthens the marketing flywheel in improving MSME business performance.